2022
DOI: 10.3389/fmed.2022.868474
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ankle Sprain Management: An Umbrella Review of Systematic Reviews

Abstract: Even though ankle sprains are among the most frequent musculoskeletal injuries seen in emergency departments, management of these injuries continues to lack standardization. Our objective was to carry out an umbrella review of systematic reviews to collect the most effective evidence-based treatments and to point out the state-of-the-art management for this injury. PubMed, Scopus, Web of Science, and the Cochrane library were searched from January 2000 to September 2020. After removing duplicates and applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…A prominent feature of ankle sprain patients is the development of ankle pain that affects their life quality (Gonzalez de Vega et al, 2013 ; Gaddi et al, 2022 ). Although the LAS model has been developed to mimic human ankle sprain, it still remains unknown whether the LAS model mice develop similar ankle joint pain as human patients.…”
Section: Resultsmentioning
confidence: 99%
“…A prominent feature of ankle sprain patients is the development of ankle pain that affects their life quality (Gonzalez de Vega et al, 2013 ; Gaddi et al, 2022 ). Although the LAS model has been developed to mimic human ankle sprain, it still remains unknown whether the LAS model mice develop similar ankle joint pain as human patients.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Kinkade’s data reported that ice applications and heat packs had matching results [ 34 ]; while Costello et al [ 35 ] established that a whole-body cryotherapy (−110 degrees C) administration provided prompt pain relief and, after 15 min, also reduced muscle tone. Lastly, ice could ensure an analgesic result, which might also facilitate therapeutic exercise in early rehabilitative phase [ 10 ]. In this scenario, it can be stated that cryotherapy, applied by a specific device, has an immediate and profound analgesic effect on severe nociceptive pain and accelerates the tissue healing process by reflex vasodilatation followed by vasoconstriction [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, a short-term immobilization with functional physiotherapy is preferable to 2/3 weeks conventional therapy with plaster [ 3 ]. Albeit, there is substantial evidence on the management of ankle injuries [ 4 , 5 , 6 , 7 , 8 , 9 ], but there is a disagreement regarding the best therapy management for acute ligament injuries in elite athletes, particularly during COVID-19 era [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some 40% of ankle sprains are at risk of chronicity. Typical features include pain on weight loading, ankle instability, and mobility issues [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines are available. However, there is a general lack of good-quality trial data in support of many current treatments [4,6,7].…”
Section: Introductionmentioning
confidence: 99%